Determinants of utilization of antenatal care services among adolescent girls and young women in Indonesia. Issue 5 (28th May 2017) - Efendi, Ferry; Chen, Ching-Min; Kurniati, Anna; Berliana, Sarni Maniar
ABSTRACT: Due to the high number of maternal deaths, provision of antenatal care services (ANC) in Indonesia is one of the key aims of the post-Millennium Development Goals agenda. This study aimed to assess the key factors determining use of ANC by adolescent girls and young women in Indonesia. Data from the Indonesia Demographic and Health Survey 2012 were used, with a focus on married adolescent girls (aged 15–19 years, n =  543) and young women (20–24 years, n =  2, 916) who were mothers. Bivariate and multiple logistic regression analyses were performed to determine the factors associated with ANC use. The findings indicated that adolescents were less likely to make ANC visits than young women. Richer women were more likely to make four ANC visits in both groups compared to the poorer women. Living in urban areas, higher educational attainment, and lower birth order were also all associated with higher levels of receiving ANC among young women. The results showed that socio-economic factors were related to the use of ANC among adolescent girls and young women. Ongoing health-care interventions should thus put a priority on adolescent mothers coming from poor socio-economic backgrounds.